The Relationship Between Training Methods And Student Activity in Extracurricular Arts SMKN 5 Padang - Assyafiah, Nada; Jamaris, Jamaris (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research was hampered by the low student activity on extracurricular arts, which was allegedly due to the inadequacy of the practice methods used. The aim is to look at the methods of practice, student activity and see the relationship between the method of practice and student activity on extracurricular arts. The research method uses a quantitative approach to the type of correlational research. The population of this research is all that follows the activity with sampling using the Cluster Random Sampling technique. Data gathering techniques using lifting. Data analysis techniques using percentage formula and Product Moment formula.The results of the study showed that; the methods of training used by trainers in extracurricular still belong to the less appropriate category; student activity also belonged to low; and there was a significant relationship between the method of training and student activity in the extra-curricular arts.Since the extracurricular activities of the arts are very beneficial to the students, there is a need for the efforts of the school to pay attention and enhance the construction of such extracursual activities. It is recommended to the extra-curricular art trainers, to increase and maximize the use of methods of training in extracural activities so as to a high level of activity.